Right to Health in the International Legal System of Human Rights at the Universal and Regional Levels - A. Yu. Yastrebova; E. E. Gulyaeva (Московский журнал международного права, 2021)
INTRODUCTION. The individual's right to health is a set of natural and positive legal frameworks that govern a person’s life activity, individual and family wellbeing, enforcement of health guarantees by the statesparticipants of universal and regional treaties of the field under question. The formation of this right stems from biological characteristics of each person, socio-economic conditions, environment, access to health and sanitation services, national health-care system progress, existence of vulnerable groups of population. Goals of the UN Sustainable Development Agenda 2030 (UN General Assembly resolution 70/1) include such essential aspects of the right to health as ending poverty and hunger in all its forms everywhere; promote food security and healthy lifestyle; the well-being of all individuals at any age; ensure availability and sustainable management of water and sanitation for all; protection and restoration of water-related ecosystems; enhancement of the States capacity to prevent and reduce national and global health risks. According to the position of the World Health Organization (WHO) the right to health imposes on the States a legal obligation to ensure timely access to adequate levels of high-quality health care, clean and safe drinking water, sanitation, adequate nutrition, shelter, health-related information and education, gender equality. As a result, the considerable amount of attention is paid to the analysis of the content of general and specific international instruments at the universal level and the international legal specificities of enshrining and maintaining an individual's right to health. The text also places the emphasis on its normative framing in the law of the Council of Europe and the European Union, reflecting the decisions and rulings of the European Court of Human Rights (ECHR).MATERIALS AND METHODS. The legal framework of the study is based on universal international treaties of the UN system, regional regulations of the Council of Europe and the EU, legal position of the UN specialized agencies, the International Committee of the Red Cross (ICRC) and the ECHR. The scientific works of domestic and foreign authors related to the study of the right to health are used as a theoretical foundation. The research uses general scientific and special cognitive techniques wherein legal analysis and synthesis, systemic, formal-legal, comparative-legal, historical-legal and dialectical methods are applied.RESEARCH RESULTS. The research indicates that the modern international legal concept of the right to health is being developed at the universal and regional level. Furthermore, specific international legal guarantees for the protection of this right are emerging for special groups such as women and children, refugees, stateless persons and migrant workers, protected persons, the wounded and the sick – all persons affected by international armed conflicts. There is a certain trend in Council of Europe and EU law towards an extended interpretation of the human right to health responding to new challenges to the realization that right, concerning bioethics, human genome editing, and the effects of nuclear testing and environmental pollution.DISCUSSION AND CONCLUSIONS. Following a review of the content and implementation of the right to health in the universal and regional international legal systems for the human rights and freedoms protection, the authors suggest its incorporation in a group of personal rights, social benefits provided by the state, and simultaneously in a collective right to development pertaining to the population as a whole. The universal international legal institutions establishing special rights for vulnerable groups will continue to be applied by member states in the context of a situational response to the global needs of families, women and children, international migration, armed conflicts, environmental conditions, and bioethical issues. The authors encourage the complement of the European system of human rights protection with an additional protocol to the Council of Europe Convention for the Protection of Human Rights and Fundamental Freedoms of 1950, involving the right to health security.